Systematic implications of leaf anatomy and palynology in the Disinae and Coryciinae (Orchidaceae) - Chesselet, Pascale Claude Marcelle Henriette (Department of Biological Sciences, 2016)
Pollen morphology of 8 species (TEM), 86 species (SEM), and leaf anatomy of 62 species (LM), were surveyed in the Oisinae, Coryclinae and, as outgroup taxa, the Orchideae and Satyriinae. Characters extracted from observations made of leaf anatomy and pollen were analysed using cladistic methods, and assessed in relation to the present phylogeny of the group. Leaf anatomy data gave little phylogenetic information. Sclerification associated with vascular bundles was systematically useful. Pollen data served to resolve taxa at the subtribal level. Both data sets provided evidence of relationship for taxonomically problematic taxa. The Coryciinae are palynologically defined by a suite of synapomorphies, including a secondarily tectate exine structure, fasciculate massulae, and elongated tetrads with linear microspore configuration. Bibliography: pages 107-123.